2018
DOI: 10.1136/jclinpath-2018-205362
|View full text |Cite
|
Sign up to set email alerts
|

A real-world, comparative study of FDA-approved diagnostic assays PD-L1 IHC 28-8 and 22C3 in lung cancer and other malignancies

Abstract: AimsAt the time of analysis, two widely used, drug-specific, tumour-cell programmed death ligand 1 (PD-L1) assays were approved by the US Food and Drug Administration for anti-PD-1 therapies: the Dako PD-L1 immunohistochemistry (IHC) 28-8 pharmDx assay and the Dako PD-L1 IHC 22C3 pharmDx assay. Given that the majority of current PD-L1 testing in US clinical practice is performed at commercial reference laboratories, we aimed to evaluate the concordance of the 28-8 and 22C3 assays in a real-world setting.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Of note, the AT-TRACTION-2 study showed that nivolumab had significant benefit in all patients, regardless of PD-L1 expression [46]. The PD-L1 IHC 28-8 pharmDx assay gained FDA approval as a complementary diagnostic test for nivolumab as second line treatment for advanced non-small cell lung cancer (NSCLC) [67].…”
Section: Ihc Of Pd-l1mentioning
confidence: 99%
“…Of note, the AT-TRACTION-2 study showed that nivolumab had significant benefit in all patients, regardless of PD-L1 expression [46]. The PD-L1 IHC 28-8 pharmDx assay gained FDA approval as a complementary diagnostic test for nivolumab as second line treatment for advanced non-small cell lung cancer (NSCLC) [67].…”
Section: Ihc Of Pd-l1mentioning
confidence: 99%
“…There are currently four FDA approved PD-L1 IHC assays as companion and/or complementary diagnostic tests, with different antibodies, cut points, scoring systems and cell specific expression associated with each test resulting in confusion in pathology labs for patients and their physicians. Since many studies have showed variable results with current assays [ 8 15 ], we have begun efforts to generate more quantitative and reproducible results. While DSP is not ready for the clinic, the technology behind the platform shows the kind of robustness and reproducibility that is typical for laboratory medicine pathology tests (generally better than IHC).…”
Section: Discussionmentioning
confidence: 99%
“…Each assay is read subjectively by a pathologist with a range of cutoffs defining expression positivity and cell specific expression either in tumor cell (TC) and/or immune cells (IC) [ 5 7 ]. Harmonization studies have been done to compare the assays within specific tumor types [ 8 15 ]. Despite strong agreement in TC PD-L1 IHC scoring among experienced pathologists, there is a poor concordance in IC PD-L1 IHC scoring or low PD-L1 scores [ 8 , 12 , 14 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IHC staining was performed using anti-PD-L1 antibody (1 : 500) (clone 28-8, Abcam, Cambridge, UK) [ 21 24 ], anti-CD4 antibody (1 : 500) (clone EPR6855, Abcam, Cambridge, UK), anti-CD8 antibody (1 : 200) (rabbit polyclonal anti-CD8, Abcam, Cambridge, UK), anti-CD163 antibody (1 : 500) (clone EPR19518, Abcam, Cambridge, UK), and anti-FoxP3 antibody (1 : 100) (clone 236A/E7, Abcam, Cambridge, UK) as the primary antibodies.…”
Section: Methodsmentioning
confidence: 99%